TOF-SIMS for carbon hybridization state analysis. (January 2022) - Drozdov, M.N.; Ieshkin, A.E.; Streletskiy, O.A.; Nishchak, O. Yu; Belykh, S.F.; Tolstoguzov, A.
Abstract: Time-of-flight secondary ion mass spectra measured for different carbon allotropes under Bi3 + cluster ion bombardment were acquired. Ion yield of homogeneous (Cn ) - and heterogeneous metal-carbon (CsCn ) - secondary cluster ions was examined. Qualitative explanation of the regularities was given based on the concept of nonlinear atomic collision cascades. It was suggested that the features of secondary cluster yield can be used for determination of hybridization state of the target material. Unlike most other techniques, secondary ion mass spectrometry is capable of the sputter depth profiling of the hybridization state. Graphical abstract: Image 1